O direito fundamental contra a autoincriminação: a análise a partir de uma teoria do Processo Penal Constitucional - Araujo, Rochester Oliveira (2013)
The right against self-incrimination is a fundamental right that works in the criminal prosecution, and therefore deserves a study supported by the general theory of criminal procedure. The right has a vague origin, and despite the various historical accounts only arises when there is a criminal procedure structured that aims to limit the State´s duty-power to punish. The only system of criminal procedure experienced that reconciles with seal self-incrimination is the accusatory model. The inquisitorial model is based on the construction of a truth and obtaining the confession at any cost, and is therefore incompatible with the right in study. The consecration of the right arises with the importance that fundamental rights have come to occupy in the Democratic Constitutional States. In the Brazilian experience before 1988 was only possible to recognize that self-incrimination represented a procedural burden for accused persons. Despite thorough debate in the Constituent Assembly, the right remains consecrated in a textual formula that´s closer to the implementation made by the Supreme Court of the United States, known as "Miranda warnings", than the text of the Fifth Amendment to the U.S. Constitution that established originally the right against self-incrimination with a constitutional status. However, the imprecise text does not prevent the consecration of the principle as a fundamental right in Brazilian law. The right against self-incrimination is a right that should be observed in the Criminal Procedure and relates to several of his canons, such as the the presumption of not guilty, the accusatory model, the distribution of the burden of proof, and especially the right of defense. Because it a fundamental right, the prohibition of self-incrimination deserves a proper study to her constitutional nature. For the definition of protected persons is important to build a material concept of accused, which is different of the formal concept over who is denounced on the prosecution. In the objective area of protection, there are two objects of protection of the norm: the instinct of self-preservation of the subject and the ability to self-determination. Configuring essentially a evidence rule in criminal procedure, the analysis of the case should be based on standards set previously to indicate respect for the right. These standard include the right to information of the accused, the right to counsel and respect the voluntary participation. The study of violations cases, concentrated on the element of voluntariness, starting from the definition of what is or is not a coercion violative of self-determination. The right faces new challenges that deserve attention, especially the fight against terrorism and organized crime that force the development of tools, resources and technologies about proves, methods increasingly invasive and hidden, and allow the use of information not only for criminal prosecution, but also for the establishment of an intelligence strategy in the development of national and public security